Структуры рудных полей и месторождений вольфрама, молибдена и олова - Макеев Б. В. Борис Васильевич; Павловский А. Б. Альфред Бернардович; Покалов В. Т. Валентин Тихонович; Фролов А. А.; Чернов Б. С. (Москва, Недра, 1983)
Авт. указаны на обороте тит. л.